ترقية مهارة كتابة اللغة العربية لطلاب الفصل الحادي عشر من خلال تطبيق طريقة الإملاء أثناء تعليم اللغة العربية في مدرسة العالية باب السلام كاليبنيغ موجواجونج جومبانج (AL-I’ROBY: Jurnal Pendidikan Bahasa Arab Dan Kebahasaaraban, 2024)
Writing is a communication activity that is carried out without the support of sound pressure, tone, expression and gestures and without gestures as occurs in oral communication activities. This study aims to: to find out the Arabic writing skills of class XI students at Madrasa Aliyah Babussalam Kalibening Mojoagung Jombang? 2) To find out how to improve Arabic writing skills for class XI students through the application of the dictation method to learning Arabic at Madrasa Aliyah Kalibening Mojoagung Jombang? 3) to find out the inhibiting and supporting factors in improving the Arabic writing skills of class XI students through the application of the dictation method to learning Arabic at MA Babussalam Kalibening Mojoagung Jombang? This study used qualitative research which sourced data from observation, interviews, documentation. The results of the research are that this research discusses the improvement of the maharah of the Arabic book through the imla method. Maharah Kitabah is a collection of words that are composed and contain meaning, because the Kitabah will not be formed unless there are regular words, with Kitabah humans can express their feelings freely according to what they think, and by pouring written expressions it is hoped that readers will understand what the author wants to express. Keywords : Maharah Kitab, the method of imla'